Environmental problem-solving : balancing science and politics using consensus building tools : guided readings and assignments from MIT's training program for environmental professionals /: balancing science and politics using consensus building tools : guided readings and assignments from MIT's training program for environmental professionals. (2019) - Susskind, Lawrence; Verdini, Bruno; Gordon, Jessica; Zaerpoor, Yasmin
No abstract available